Sustainable Banking in Practice: Stakeholder Responses and Implementation Challenges in a Regional Bank - Hadi Prabowo; Yunieta Anny Nainggolan (Integrasi Sains Media, 2025)
This study analyses the adoption of Environmental, Social, and Governance (ESG) principles in a regional development bank in Indonesia via the perspective of Stakeholder Theory. Using a qualitative approach, the research analyses how the bank connects with and responds to its internal and external stakeholders within the framework of national rules, particularly POJK 51/2017 and the Indonesian Green Taxonomy. Although the bank has demonstrated formal compliance, as evidenced by submitting Sustainable Finance Action Plans and releasing GRI-based sustainability reports, findings indicate that ESG integration remains inconsistent across units and functions. Major problems include insufficient ESG literacy among employees, the absence of stakeholder-oriented performance metrics, fragmented ESG-related data systems, and a lack of organised engagement tools that facilitate dialogue and responsiveness. Despite these impediments, positive indications from stakeholders, such as increased public awareness and substantial investor interest in sustainability bonds, reflect the growing reputational value of ESG commitments. However, the study reveals that stakeholder engagement strategies are primarily one-directional, with limited institutional frameworks for co-creation, feedback, or collaborative governance. To address these shortcomings, the report advises constructing inclusive stakeholder forums, embedding ESG indicators into key performance metrics, centralizing ESG data infrastructure, and conducting organised capacity-building programs. This study contributes to the growing discourse on stakeholder-responsive ESG implementation in regional banking, providing strategic insights for enhancing trust, inclusion, and long-term sustainability performance.